Efficiency and Economy in the Irrigation and Power Sector Ministry of Irrigation and Power - Planning Commission (Planning Commission, 1957)
This matter was discussed at the symposium held at the time of the 27th meeting of the Central Board of Irrigation & Power at Bombay. The symposium recommended that each State should forthwith establish the water resources investigation unit under the charge of an officer not lower than the rank of a superintending engineer with a proper compliment of junior staff and an experienced and competent agricultural officer, fully conversant with the soils, drainage conditions and agricultural practices in different areas of the State. The symposium further recommended that the detailed project reports and estimates for the Third Five Year Plan must be completed not later than by the middle of 1960.
Ministry of Irrigation and Power